Model-Model Pembelajaran Efektif dan Inovatif dalam Mata Pelajaran Sains (IPA) – (Cooperative Learning) - Masruri (Cakrawala: Jurnal Pendidikan, 2022)
This study aims to understand how to understand effective and innovative models applied in science learning. Modifications, especially to some teaching methods, are made entirely in the context of development or adjustment to needs. Learning design is the practice of compiling communication technology media and content to assist in the effective transfer of knowledge between teachers and students. Learning design is also a design for the learning process based on learning needs and objectives and the delivery system so that it becomes a reference in its implementation to create effective and efficient learning by minimizing students' difficulties in understanding learning. On the personal development of students by paying more attention to the life of the realm of taste, especially the emotional side. The help of the personal model clump is more emphasized on the formation and organization of the unique realities of environmental life and life. It is hoped that by using this learning model the teaching and learning process can help students develop their own productive relationships with their environment. Students as students can also realize themselves as "personal" who are skilled enough to interact with outsiders so as to produce a conducive pattern of interpersonal relationships.